Scholarly journal publishing in Australia. Issue 2 (21st January 2022) - Jamali, Hamid R.; Wakeling, Simon; Abbasi, Alireza
Abstract: This article describes the nature and extent of scholarly journal publishing in Australia. Australian journals are defined as journals that belong to or are affiliated with an Australian entity. There are currently 651 active Australian journals. The oldest started in the 19th century, and the 1990s was the top decade in terms of starting new journals. Australian journals mostly belong to or are affiliated with non‐profit organizations (e.g., learned societies) (364, 55.9%), or educational institutions (168, 25.8%). While most of the journals (426, 65.4%) are published by their owners (self‐publish), the publication of 162 journals has been outsourced to international commercial publishers, with most of these linked to non‐profit organizations. About 39.8% of Australian journals are open access and most of them do not charge author‐processing charges. Half of the Australian journals (326) are indexed in Scopus and slightly less than half (301) are included in Web of Science (WoS). Arts, Humanities and Social Sciences are well represented in the disciplinary focus of journals, although journals indexed in Scopus and WoS are more likely to be in health, life and physical science disciplines.